Genetics, Host Range, and Molecular and Pathogenic Characterization of Verticillium dahliae From Sunflower Reveal Two Differentiated Groups in Europe - Martín-Sanz, Alberto; Rueda, Sandra; García-Carneros, Ana B.; González-Fernández, Sara; Miranda-Fuentes, Pedro; Castuera-Santacruz, Sandra; Molinero-Ruiz, Leire (Frontiers in Plant Science, 2018)
Verticillium wilt and leaf mottle (VWLM), caused by the fungus Verticillium dahliae Kleb. (Vd), has traditionally been a major disease of sunflower in Argentina and the USA (Gulya et al., 1997; Radi and Gulya, 2007; Galella et al., 2012) as well as in temperate European countries (Harveson and Markell, 2016). However, disease incidence in France, Italy, Spain and countries around the Black Sea has dramatically increased in recent years and in some regions, like southern France, it is becoming a major constraint to sunflower oil production (Harveson and Markell, 2016; Debaeke et al., 2017). Verticillium dahliae is a soilborne ascomycete with a wide range of host crops. Besides sunflower, it causes important yield losses in artichoke (Cynara cardunculus L. var. scolymus), cauliflower (Brassica oleracea var. botrytis L.), cotton (Gossypium hirsutum L.), eggplant (Solanum melongena L.), lettuce (Lactuca sativa L.), olive tree (Olea europaea L.), potato (Solanum tuberosum L.), tobacco (Nicotiana tabacum L.) and tomato (Solanum lycopersicum L.), among others (Pegg and Brady, 2002). In Spain, Verticillium constitutes an important constraint for the production of cotton, artichoke, and, particularly, of olive tree (Bejarano-Alcázar et al., 1996; Berbegal et al., 2010; Jiménez-Díaz et al., 2011; López-Escudero and Mercado-Blanco, 2011). Also in Spain, VWLM outbreaks have repeatedly been observed in the last few years in sunflower fields of Cadiz province (García-Ruiz et al., 2014), where it is grown in alternation with other crops, particularly cotton and/or tomato. Some fields have in fact even been turned into olive tree groves. Host specialization occurs in Vd, meaning that isolates from a given host may be pathogenic on other hosts but, generally, they are more virulent (symptoms are more severe) on the hosts from which they were obtained. In some Vd isolates, host specialization is more pronounced (Bhat and Subbarao, 1999; Douhan and Johnson, 2001). In areas where sunflower is grown in alternation with other crop species, determination of the host range specificity of Vd affecting sunflowers is important for the correct management of the whole cropping system.